MEHRSTIMMIGKEIT UND TONSYSTEME IN ZENTRAL- UND OSTAFRIKA. Bemerkungen zu den eigenen, im Phonogrammarchiv der Osterreichischen Akademie der Wissenschaften archivierten Expeditionsaufnahmen. Gerhard Kubik. Communication No. 83 of the Phonogram Archive Commission of the Austrian Academy of Sciences. Vienna, 1968. - Nurse, George T. (International Library of African Music, 1969)
pages: 105
Keywords: African Music